Myocardial Immunocompetent Cells and Macrophage Phenotypes as Histopathological Surrogates for Diagnosis of Cardiac Sarcoidosis in Japanese. Issue 11 (17th November 2016) - Honda, Yasuyuki; Nagai, Toshiyuki; Ikeda, Yoshihiko; Sakakibara, Mamoru; Asakawa, Naoya; Nagano, Nobutaka; Nakai, Michikazu; Nishimura, Kunihiro; Sugano, Yasuo; Ohta‐Ogo, Keiko; Asaumi, Yasuhide; Aiba, Takeshi; et al.
Abstract : Background: The histological diagnosis of cardiac sarcoidosis (CS) is based on the presence of myocardial granulomas; however, the sensitivity of endomyocardial biopsy is relatively low. We investigated whether immunocompetent cells including dendritic cells (DC) and macrophages in nongranuloma sections of endomyocardial biopsy samples could be histopathological surrogates for CS diagnosis. Methods and Results: The numbers of DC and macrophages were investigated in 95 consecutive CS patients and 50 patients with nonischemic cardiomyopathy as controls. All patients underwent endomyocardial biopsy, and immunohistochemical staining was performed on all samples. We examined these immunocompetent cells in nongranuloma sections in CS patients diagnosed by the presence of myocardial granulomas (n=26) and in CS patients without myocardial granulomas diagnosed by the Japanese Ministry of Health Welfare 2007 criteria (n=65) or the Heart Rhythm Society 2014 criteria (n=26). In CS patients with and without myocardial granulomas, CD209 + DC and CD68 + macrophages were more frequently observed ( P <0.01) and CD163 + M2 macrophages were less frequently observed ( P <0.01) in nongranuloma sections compared to controls. Furthermore, the combination of decreased CD163 + M2/CD68 + macrophage ratio and increased number of CD209 + DC in nongranuloma sections of CS patients demonstrated high specificity (100%, 95% CI 92.7–100) for CS diagnosis with each diagnostic criteria and the presence of myocardial granulomas. Conclusions: Increased number of DC and decreased M2 among all macrophages in nongranuloma sections of myocardium showed high specificity for CS diagnosis, suggesting DC and macrophage phenotypes as histopathological surrogates for the diagnosis of CS.